2018
DOI: 10.2147/phmt.s176114
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes about acquiring a dental home for preschool children: a new concept in the Arab state of Qatar

Abstract: ObjectiveThe purpose of the study was to assess parental perceptions and acceptability of a dental home for their preschool children, a new concept in the state of Qatar.MethodsA cross-sectional prospective study was conducted at Hamad Medical Corporation, in the state of Qatar. Parents of infants and children <5 years of age were offered an interview survey.ResultsA total of 309 questionnaires were completed (response rate =98%). More than 90% of the participants believed that oral health and dentition affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…From the results, the prevalence of luoride treatment in this study was observed to be 37.7%. Our study is in concordance with previous literature and reports a low incidence of luoride treatment in pediatric dentistry (Chi, 2014;Hendaus et al, 2018). These can be attributed to the fact that many parents are not aware of luoride treatment and refuse; however, on awareness can accept the treatment.…”
Section: Resultssupporting
confidence: 93%
“…From the results, the prevalence of luoride treatment in this study was observed to be 37.7%. Our study is in concordance with previous literature and reports a low incidence of luoride treatment in pediatric dentistry (Chi, 2014;Hendaus et al, 2018). These can be attributed to the fact that many parents are not aware of luoride treatment and refuse; however, on awareness can accept the treatment.…”
Section: Resultssupporting
confidence: 93%
“…Oral health related quality life measures the degree to which oral problems disrupt normal social functioning and lead to major changes in activities of daily living, such as the ability to work or attend school [2,3] and overall impact on emotional and functional well-being [4]. Oral health of children is of particular importance because children who experience early childhood caries are at higher risk for developing gingivitis, periodontal disease, and other dental problems as they age [5]. Dental care is a common unmet health need in U.S. children [6], associated with the highest financial barriers compared to other areas of health care [7].…”
Section: Introductionmentioning
confidence: 99%
“…At 5 years of age, both absolute and relative inequalities were observed, with a difference of 14 percentage points in dental pain frequency among the children of more educated and less educated mothers and 13 percentage points among the most extreme quintiles of household income. The oral health condition in this age group may be influenced by the use of oral health services and the knowledge of caregivers about the importance of deciduous dentition 20‐22 . Also, some infectious processes in deciduous dentition may not be reported by the child or perceived by parents, because caregivers’ perception may be influenced by issues related to one's own context.…”
Section: Discussionmentioning
confidence: 99%